2019
DOI: 10.4274/balkanmedj.galenos.2019.2019.1.130
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Affect of Predominant Histologic Subtypes in Resected Pulmonary Adenocarcinoma Predominant Subtypes of Pulmonary Adenocarcinoma

Abstract: Background:Predominant histologic subtypes have been reported as predictors of survival of patients with pulmonary adenocarcinoma.Aims:To evaluate the predictive value of histologic classification in resected lung adenocarcinoma using the classification systems proposed by the International Association for the Study of Lung Cancer, American Thoracic Society, European Respiratory Society, and World Health Organization (2015).Study Design:Cross-sectional study.Methods:The histologic classification of a large coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…We found a higher incidence of solid and micropapillary predominant adenocarcinoma compared to that in the open-source data. 14 , 30 Meanwhile, patients with lepidic-predominant lung adenocarcinoma were lower in our study than in previous reports, 10 , 31 reiterating adenocarcinoma with high-grade patterns had a higher risk of recurrence than those with other adenocarcinoma subgroups. 11 …”
Section: Discussioncontrasting
confidence: 72%
“…We found a higher incidence of solid and micropapillary predominant adenocarcinoma compared to that in the open-source data. 14 , 30 Meanwhile, patients with lepidic-predominant lung adenocarcinoma were lower in our study than in previous reports, 10 , 31 reiterating adenocarcinoma with high-grade patterns had a higher risk of recurrence than those with other adenocarcinoma subgroups. 11 …”
Section: Discussioncontrasting
confidence: 72%
“…However, other studies reported that adenocarcinoma, as a poor prognostic determinant in resected lung cancer, appeared to have a higher recurrence rate than non-adenocarcinoma. 19,20 It might be explained that for postoperative patients of stage I, adenocarcinoma was more likely to have distant metastasis, while squamous cell carcinoma was more likely to have local recurrence. 21 The T stage has always been an independent risk influence affecting prognosis after stage I NSCLC.…”
Section: Discussionmentioning
confidence: 99%